2011
DOI: 10.1186/1477-5751-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the CXCR1 gene (IL8RA) is not associated with susceptibility to chronic periodontitis

Abstract: BackgroundThe chemokine receptor 1 CXCR-1 (or IL8R-alpha) is a specific receptor for the interleukin 8 (IL-8), which is chemoattractant for neutrophils and has an important role in the inflammatory response. The polymorphism rs2234671 at position Ex2+860G > C of the CXCR1 gene causes a conservative amino acid substitution (S276T). This single nucleotide polymorphism (SNP) seemed to be functional as it was associated with decreased lung cancer risk. Previous studies of our group found association of haplotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…For instance, MO‐BN reveals that a cxcr1 SNP (Rs2234671) plays a dual role in RP2 and LC responses. This is corroborated by literature where it was reported that the cxcr1 SNP mediates inflammatory response through IL‐8, and it was also found to predict tumor response . Moreover, miRNAs in our MO‐BNs act as master regulators of biophysical pathways.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, MO‐BN reveals that a cxcr1 SNP (Rs2234671) plays a dual role in RP2 and LC responses. This is corroborated by literature where it was reported that the cxcr1 SNP mediates inflammatory response through IL‐8, and it was also found to predict tumor response . Moreover, miRNAs in our MO‐BNs act as master regulators of biophysical pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the −1026 SNP, we found that individuals carrying the (AC) or (AA) genotypes were more susceptible to CP. However, similar to other studies [ 36 , 38 ], this genetic association was not maintained after the adjustments for covariates in the multiple logistic regression analysis. Multiple logistic regressions were used here to evaluate the influence of common (and other potential) covariates, in the association of each NOS2 SNP with CP.…”
Section: Discussionsupporting
confidence: 83%
“…One study [ 20 ] involving rs2234671 polymorphism showed it was not related to periodontitis risk (C vs. G: OR = 1.10, 95%CI = 0.67–1.79, p = 0.71; CG+CC vs. GG: OR = 1.12, 95%CI = 0.66–1.90, p = 0.68).…”
Section: Resultsmentioning
confidence: 99%